Etika Bisnis Dalam Islam - Suchamdi Suchamdi (Justicia Islamica, 2006)
This study aims to analyze the concept of business ethics in Islam and its application in modern trade and economic practices. Islam emphasizes the principles of honesty, justice, and the prohibition of usury, uncertainty, and luck in business activities. This study uses a qualitative method with a literature study approach, examining primary sources such as the Qur'an, Hadith, and the thoughts of scholars regarding Islamic business ethics. The results showed that Islamic business ethics are oriented towards a balance between economic profit and moral responsibility, which is reflected in the concept of halal-haram, transparency in transactions, and social concern through zakat and almsgiving. The implementation of Islamic business ethics in the modern era still faces challenges, especially in a competitive global economic system. This study emphasizes that the application of Islamic business ethics can create a fairer, more sustainable, and welfare-oriented trading ecosystem.